2016
DOI: 10.1103/physrevb.93.165434
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical analysis of two-dimensional boron monolayers

Abstract: Using density functional theory calculations (both perturbed and unperturbed) as well as thermodynamic and ballistic transport equations, what follows investigates thermal and mechanical properties of 2D boron monolayers (δ 6 -, α-, δ 5 -, and χ 3 -sheets with respective vacancy densities η = 0, 1/9, 1/7, 1/5) as they relate to the vacancy density. The triangular (δ 6 ) sheet's room-temperature phonon and electron thermal conductances are found to respectively be roughly 2.06 times and 6.60 times greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
8
42
0
Order By: Relevance
“…the ballistic thermal transport of δ 6 borophene. [91] The results of phonon thermal conductance agreed well with that from Zhou et al [34] Li et al studied the quantum lattice thermal conductance of C-borophane. [37] Interestingly, the B-H group is isoelectronic with C and its mass is also similar to C. It was found that hydrogenation only slightly decreases the thermal conductance of δ 6 borophene while hydrogenation can obviously reduce the thermal conductance of graphene.…”
Section: Ballistic Thermal Transport Of Borophenesupporting
confidence: 83%
See 3 more Smart Citations
“…the ballistic thermal transport of δ 6 borophene. [91] The results of phonon thermal conductance agreed well with that from Zhou et al [34] Li et al studied the quantum lattice thermal conductance of C-borophane. [37] Interestingly, the B-H group is isoelectronic with C and its mass is also similar to C. It was found that hydrogenation only slightly decreases the thermal conductance of δ 6 borophene while hydrogenation can obviously reduce the thermal conductance of graphene.…”
Section: Ballistic Thermal Transport Of Borophenesupporting
confidence: 83%
“…Furthermore, the interaction force strength between boron atoms in the armchair direction is about 30 times of that in the zigzag direction, showing stronger thermal transport anisotropy than other 2D materials. Tasfack and Yakobson also studied the ballistic thermal transport of δ 6 borophene . The results of phonon thermal conductance agreed well with that from Zhou et al…”
Section: Thermal Transport Of Borophenesupporting
confidence: 79%
See 2 more Smart Citations
“…Recently, borophene came into researchers' sight because of its unique position close to carbon and it is the lightest Xenes. The polymorphism and anisotropic structure of borophene lead to many attractive properties, including the optical transparency, metallicity, phonon‐mediated superconductivity, photoluminescence in visible region (≈626 nm), efficient thermal transport, mechanical flexibility, etc. When considering its photothermal application, there is a drawback of weak absorption with extinction coefficient of ≈2.5 L g −1 cm −1 , making the application of photothermal evaporation full of challenge.…”
Section: Photothermal Evaporationmentioning
confidence: 99%